Gene expression profiling by massively parallel sequencing - Torres, Tatiana Teixeira; Metta, Muralidhar; Ottenwälder, Birgit; Schlötterer, Christian (Genome Research, 2008)
Massively parallel sequencing holds great promise for expression profiling, as it combines the high throughput of SAGE with the accuracy of EST sequencing. Nevertheless, until now only very limited information had been available on the suitability of the current technology to meet the requirements. Here, we evaluate the potential of 454 sequencing technology for expression profiling using Drosophila melanogaster. We show that short (< ∼80 bp) and long (> ∼300–400 bp) cDNA fragments are under-represented in 454 sequence reads. Nevertheless, sequencing of 3′ cDNA fragments generated by nebulization could be used to overcome the length bias of the 454 sequencing technology. Gene expression measurements generated by restriction analysis and nebulization for fragments within the 80- to 300-bp range showed correlations similar to those reported for replicated microarray experiments (0.83–0.91); 97% of the cDNA fragments could be unambiguously mapped to the genomic DNA, demonstrating the advantage of longer sequence reads. Our analyses suggest that the 454 technology has a large potential for expression profiling, and the high mapping accuracy indicates that it should be possible to compare expression profiles across species.
10.1101/gr.6984908